Efektivitas Model Game Based Learning dalam Pembelajaran Bahasa Indonesia Kelas XII IPS SMA Bima Ambulu - Irfan Kholid Sofhan; Nuning Indahwiya; Agus Milu Susetyo (Jurnal Ilmu Bahasa dan Pendidikan Guru Sekolah Dasar, 2026)
This research is motivated by the use of conventional learning models that still dominate Indonesian language learning at the high school level, causing learning to become monotonous and less actively involving students. This study aims to determine the effectiveness of implementing the Quizizz-based Game Based Learning (GBL) model in improving learning outcomes, motivation, and participation of grade XII Social Science students at SMA BIMA Ambulu. The research method used is quantitative experimental with a one-group design (one-group pretest-posttest design). Research subjects consisted of 70 students divided into two classes, namely XII IPS 2 and XII IPS 5, with 35 students each. Data were collected through tests (pretest and posttest), learning motivation questionnaires using a 5-level Likert scale, student activity observation sheets, and documentation of learning activities. Research instruments have been tested for validity using Pearson Product Moment correlation and reliability using Cronbach's Alpha. Data analysis included validity tests, reliability tests, normality tests, and hypothesis testing using Independent Sample t-Test. The research results show that all test items are declared valid (r calculated > r table 0.334) and the instrument is reliable with a Cronbach's Alpha value of 0.812. The average N-Gain for class XII IPS 2 is 0.668 and class XII IPS 5 is 0.679, both in the medium-high category indicating the effectiveness of the GBL model. The t-test results show no significant difference between the two classes (mean difference 0.011), indicating consistency in the effectiveness of the GBL model in both groups. This study concludes that the Quizizz-based Game Based Learning model is proven effective in improving Indonesian language learning outcomes for grade XII Social Science students at SMA BIMA Ambulu. The implementation of GBL creates more interactive, enjoyable, healthy competitive learning, and is able to increase motivation and active student participation in learning.